Deposition, opto-electronic and structural characterization of polymorphous silicon thin films to be applied in a solar cell structure. (February 2015) - Hamui, L.; Remolina, A.; García-Sánchez, M.F.; Ponce, A.; Picquart, M.; López-López, M.; Monroy, B.M.; Santana, G.
Abstract: In this study we analyze the optoelectronic properties and structural characterization of hydrogenated polymorphous silicon thin films as a function of the deposition parameters. The films were grown by plasma enhanced chemical vapor deposition (PECVD) using a gas mixture of argon (Ar), hydrogen (H2 ) and dichlorosilane (SiH2 Cl2 ). High-resolution transmission electron microscopy images and Raman measurements confirmed the existence of very different internal structures (crystalline fractions from 12% to 54%) depending on the growth parameters. Variations of as much as one order of magnitude were observed in both the photoconductivity and effective absorption coefficient between the samples deposited with different dichlorosilane/hydrogen flow rate ratios. The optical and transport properties of these films depend strongly on their structural characteristics, in particular the average size and densities of silicon nanocrystals embedded in the amorphous silicon matrix. From these results we propose an intrinsic polymorphous silicon bandgap grading thin film to be applied in a p–i–n junction solar cell structure. The different parts of the solar cell structure were proposed based on the experimental optoelectronic properties of the pm-Si:H thin films studied in this work.